Protocol matters: A need for standardized procedure in cementochronology - Zazvonilová, Eliška; Velemínský, Petr; Černíková, Alena; Danielisová, Alžběta; Brůžek, Jaroslav (Forensic science international, 2022)
Cementochronology has long been associated in the literature with a high correlation between chronological and estimated age, and low differences between the two ages. The excessive accuracy was rather suspicious, and the method did not even appear in common forensic practice. An important step towards more widespread use of the method is the need to standardize work procedures, including indexes for recording the quality of cementum, preparation of thin sections and the age calculation. In our study, we used the standardized protocol for the preparation of thin sections in a set of Czech modern teeth of known age and sex. In the initial phase, 11.5% of the teeth were discarded due to severe caries in the medial part of the root. In a set of single extractions (55 teeth from 55 individuals), we focused on the detailed results of the age estimation, using precision and accuracy indicators. We also used different dental development data to calculate age, given inconsistencies in the use of eruption / mineralization. In a set of multiple extractions (68 teeth from 22 individuals), intra-individual variability was examined. The result of the application of the standardized protocol is an estimate of age with an absolute inaccuracy of -1.7 years and a relative inaccuracy of 5.4%. Calculation of precision and accuracy in the set of single extractions, however, showed the method's limitations: the imprecision measuring the variability of cementum increments counts increased with chronological age, as did the inaccuracy. The use of different dental development data did not significantly increase the accuracy of the age estimation results. Intra-individual variability remains poorly understood - in the set of multiple extractions the differences within one individual ranged between 0.9 and 10.8 years.
Keywords: Age Determination by Teeth; Protocol; lidé; Age-at-death estimation; určení zubního věku; Validation; Tooth Eruption; Czech modern population; Standardization; prořezávání zubů; Cementochronology; Humans